2021
DOI: 10.21608/aimj.2021.55810.1390
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Endometrial Histopathology in Postmenopausal Uterine Bleeding and Transvaginal Colour Doppler

Abstract: Background: Correlation Between Endometrial Histopathology in Postmenopausal Uterine Bleeding and Transvaginal Colour Doppler. Aim of the work: To evaluation of transvaginal ultrasound and transvaginal color doppler of uterine arteries compared to endometrial histopathology in Postmenopausal uterine bleeding. Patients and methods: Prospective comparative observational cohort study. This study involving 90 patients complaining postmenopausal bleeding recruited from those attending in the Gynecology clinic in Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…in Egypt. [ 17 ] In a study by Madkour signs of multiple angiogenesis were found in 7/10 cancer cases, remaining 1 case of disseminated vascular proliferation and 2 cases of no Doppler signal. [ 8 ] The LR (+) index was 16.0, showing signs of multiple vascular proliferations that were valuable for diagnosing EC in our study [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…in Egypt. [ 17 ] In a study by Madkour signs of multiple angiogenesis were found in 7/10 cancer cases, remaining 1 case of disseminated vascular proliferation and 2 cases of no Doppler signal. [ 8 ] The LR (+) index was 16.0, showing signs of multiple vascular proliferations that were valuable for diagnosing EC in our study [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 El Kady et al study revealed that, atrophic endometrium was the most common finding (26/90=28.9%), hyperplasia without atypia in (36/90=40.0%), hyperplasia with atypia (18/90=20.0%) and endometrial carcinoma was found in (10/90=11.11%). 14 Ebrashy et al examined 65 cases by both TVS 2D and 3D ultrasound and the results were by 2D ultrasound: 20% were normal, 10.67% showing endometrial polyps, 44.61% having myomas either single or multiple, 18.46% had thickened endometrium while by 3D ultrasound: 13.84% were normal. 15 Odeh et al evaluated the accuracy of endometrial volume measurement in the diagnosis of endometrial carcinoma and endometrial hyperplasia and found that 17.9% of patients had an endometrial polyp, 12.5% had hyperplasia and 7.6% had endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%